1)
![(a-b)(a-b)=a^2-b^2](https://img.qammunity.org/2023/formulas/mathematics/college/fiw337w3mks9fgrujst0e64gjhbjf2yaih.png)
we can use the distribution propertie:
![\begin{gathered} (a-b)(a-b)=a^2-ab-ab+b^2 \\ (a-b)(a-b)=a^2-2ab+b^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/h2ztpo1kkwlftmvayap9rkb2ksn57htg1t.png)
Is false
2)
![(a+b)(a+b)=a^2+2ab+b^2](https://img.qammunity.org/2023/formulas/mathematics/college/h7uc985kggyzrz96mb94dts5is8ootu85g.png)
Again, we can use the distribution propertie:
![\begin{gathered} (a+b)(a+b)=a^2+ab+ab+b^2 \\ (a+b)(a+b)=a^2+2ab+b^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mnm3qhemw2i1pueoc6pwpn3wybrw7tgkys.png)
Is true
3) is the same as the numeral 1) so in this case the experession is true
4)
![(a+b)(a-b)=a^2+2ab-b^2](https://img.qammunity.org/2023/formulas/mathematics/college/e6x7i604qe57hbgh9r7vymez72v6936jpy.png)
Again, we can use the distribution propertie:
![\begin{gathered} (a+b)(a-b)=a^2-ab+ab-b^2 \\ (a+b)(a-b)=a^2-b^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/iiijsfh93sgxhctfeig9gadhnjca56jgjo.png)
Is false
5) is the same as the numeral 4) so in this case is true
6)
![(a+b)(a+b)=a^2+b^2](https://img.qammunity.org/2023/formulas/mathematics/college/rf6i7it51xsm69tqia5w0gy3u9alszc8ap.png)
Using the distribution:
![\begin{gathered} (a+b)(a+b)=a^2+ab+ab+b^2 \\ (a+b)(a+b)=a^2+2ab+b^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mnm3qhemw2i1pueoc6pwpn3wybrw7tgkys.png)
So is false